Resolution of two-color quantum imaging with undetected photons - Vega, Andres; Santos, Elkin; Fuenzalida, Jorge; Basset, Marta Gilaberte; Pertsch, Thomas; Gräfe, Markus; Saravi, Sina; Setzpfandt, Frank (Optics InfoBase Conference Papers, 2021)
We analyze the diffraction-limited resolution of quantum imaging with undetected photons with non-degenerate photon-pairs. We find that the resolution is half of the longest of both wavelengths and is achieved using sources with sub-wavelength thicknesses.
CRIS-Team Scopus Importer:2023-04-20